How COVID-19 Impacted The Tacit Knowledge and Social Interaction of Global NPD Project Teams: The complexity framework offers managers an effective way to analyze problems and to generate solutions to manage tacit knowledge and social interaction in dispersed global NPD project teams. Issue 2 (22nd February 2022) - Cecchi, Michele Angelo; Grant, Stuart; Seiler, Matthias; Turner, Neil; Adams, Richard; Goffin, Keith
: Overview: Multinational, technology-intensive companies routinely use globally distributed R&D teams, but COVID-19 represented an additional challenge. Lockdowns and home-office working severely limit human interaction and can impact the communication, social interaction, and knowledge sharing critical to successful R&D. Our study investigated how COVID-19 affected R&D processes at three global companies, using a project complexity perspective. Although R&D managers responsible for global projects are accustomed to the challenges of managing communications, the fact that teams were forced into home-office working made new product development more difficult in several ways. Ensuring that technical details are understood by all members of dispersed teams is crucial. Of particular note, and central to our findings, is the emphasis that R&D managers placed on maintaining a high level of social interaction in their teams, and special efforts were needed to keep interactions at a sufficient level to foster the generation and transfer of tacit knowledge. The findings have strong implications for the way that R&D project management is likely to be conducted in a post-COVID-19 world, and we demonstrate how the complexity framework we used can benefit managers in navigating this and other challenges.